(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Wound healing is a complex biological process that involves a cascade of cellular and molecular events. Pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) play a crucial role in initiating and orchestrating the inflammatory phase of wound healing. The determination of wound age is essential in forensic investigations. However, traditional methods for wound age estimation can be subjective and unreliable. This study investigated the correlation between pro-inflammatory cytokine levels (IL-1β, IL-6, and TNF-α) in human dermal wounds and the known wound age. A two-year prospective study was conducted on autopsy cases with documented wound infliction time. The samples were collected from the wound margin, and cytokine levels were measured using ELISA. Results demonstrated a significant (p = 0.001) relationship between TNF-α levels and wound age for a postmortem period between 12 and 24 hours. The concentrations of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) are consistently higher in wound margin samples compared to control samples with a statistically significant difference in their levels. However, the relevance of IL-6 and IL-1β levels at wound margin decreases beyond first hours of wound age. The wound margin TNF-α level is a significant biomarker for the estimation of wound age within the first 24 hours of injury. These findings suggest that the pro-inflammatory cytokine level changes in the wound margin could be a potential biomarker for estimating postmortem wound age with certain limitations of duration (